2019
DOI: 10.1111/soin.12264
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Management and Resistance among High‐Achieving Undocumented Students

Abstract: Based on 32 in‐depth interviews with undocumented students at four‐year colleges and college graduates in Southern California, this study examines the stigma management and resistance practices undocumented students employ in an educational context. Shock, shame, embarrassment, and fear of deportation initially cause them to employ a variety of stigma management methods to keep their status secret while accepting its negative societal evaluation. However, the experience of higher education facilitates the stig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…The act of suppressing one's identity for fear of rejection, discrimination, or for any other reason can be emotionally damaging. Consistent with the findings of this study, research studies identify secrecy and shame as central to the development of negative self-concept among undocumented college students (Yasuike, 2019). Participants in this study shared the stigma and shame they felt about being DACA, and the pressure they felt to hide it from their peers in order to be socially accepted.…”
Section: Theoretical and Policy Implicationssupporting
confidence: 82%
“…The act of suppressing one's identity for fear of rejection, discrimination, or for any other reason can be emotionally damaging. Consistent with the findings of this study, research studies identify secrecy and shame as central to the development of negative self-concept among undocumented college students (Yasuike, 2019). Participants in this study shared the stigma and shame they felt about being DACA, and the pressure they felt to hide it from their peers in order to be socially accepted.…”
Section: Theoretical and Policy Implicationssupporting
confidence: 82%
“…" (pp. 77-78) Although students may be cognizant of their own or family members' citizenship statuses at younger ages, the societal implications are often delayed (Benuto et al, 2018;Gerrard & Vivian, 2022;Gonzales, 2011;Sánchez et al, 2022;Yasuike, 2019).…”
Section: K-12 Schoolingmentioning
confidence: 99%
“…Although some high-achieving students may adopt meritocratic ideals-believing that hard work leads to success-systemic barriers can impact undocumented students' educational and life outcomes (Abrego, 2006;Gerrard & Vivian, 2022;Sánchez et al, 2022;Yasuike, 2019). Students may alter their aspirations to pursue different majors or career paths based on citizenship statusrelated issues (Abrego, 2006;Gonzales, 2011;Patler, 2018;Yasuike, 2019). For example, Patler (2018) found that one undocumented student decided to withdraw from teacher education because of anticipated background checks in the teaching profession that required fingerprinting.…”
Section: Navigating Higher Educationmentioning
confidence: 99%
“…Students may also encounter racist-nativist microaggressions, anti-immigrant sentiment, or explicitly hostile environments (Muñoz & Vigil, 2018;Shelton, 2019;Suárez-Orozco et al, 2015). Such experiences may be stigmatizing and contribute to social-emotional barriers to support seeking (Muñoz, 2016;Pérez Huber, 2010;Yasuike, 2019). Ultimately, exclusionary campus experiences may prevent undocumented students from accessing academic support services.…”
Section: Campus Exclusionmentioning
confidence: 99%